On Dostoyevsky’s "antisocialism" - Serdiutchenko, V. (Literatūra, 1974)
The present paper contains some observations on social and historical motives of Dostoyevsky’s "antisocialism". The author reasons that in Dostoyevsky’s epoch scientific socialism was far from being a prevailing current among all other trends of socialist ideas and that in the 19th c. theoretical socialism was more often presented in its extremes than in its true conception. Therefore, Dostoyevsky’s antisocialist criticism, as a rule, was directed against the misleading socialist ideas of his own epoch. On the other hand, socialist conceptions were not acceptable for Dostoyevsky because they were usually based on the materialistic world outlook, whereas Dostoyevsky was an idealist, no matter whether his idealistic views were reactionary or democratic.